2014
DOI: 10.3402/tellusa.v66.24065
|View full text |Cite
|
Sign up to set email alerts
|

The importance of using a high-resolution model to study the climate change on small islands: the Lesser Antilles case

Abstract: A B S T R A C T High-resolution climate change simulations over the Lesser Antilles are performed using the ALADIN-Climate regional climate model nested within the global model ARPEGE (Me´te´o-France). Three sets of simulations are conducted at 10 km grid spacing for reference (1971Á2000) and future climate (2071Á2100) under two CMIP5 scenarios (RCP4.5 and RCP8.5). With the dynamical downscaling, islands of Lesser Antilles are considered as land by the model, whereas, for the driving model, there is only sea o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Credible estimates of climate variables are the basis and premise of the assessment of the climate change impacts, while the high resolution of simulation is one of the decisive factors, especially for wind, precipitation and extreme climate variables, which are mainly subjected to regional terrains, vegetation, convection and so on. In terms of the importance of high resolution, Cantet et al found that high‐resolution simulation in temperature showed remarkable advantages over small islands. Lee and Hong thought that the finer resolution model was more efficient in producing the major characteristics the precipitation distribution and temperature distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Credible estimates of climate variables are the basis and premise of the assessment of the climate change impacts, while the high resolution of simulation is one of the decisive factors, especially for wind, precipitation and extreme climate variables, which are mainly subjected to regional terrains, vegetation, convection and so on. In terms of the importance of high resolution, Cantet et al found that high‐resolution simulation in temperature showed remarkable advantages over small islands. Lee and Hong thought that the finer resolution model was more efficient in producing the major characteristics the precipitation distribution and temperature distribution.…”
Section: Introductionmentioning
confidence: 99%
“…As we aim to evaluate the climate change effects on the energy budget components, we also used the RCM output, instead of the station observations, to drive the LSM. Currently, horizontal resolutions of some RCMs are around 10 km (e.g., references [67][68][69][70][71]). This is sufficiently high to infer the general characteristics of the energy and hydrologic cycles for large and medium scale basins, though still quite coarse to allow the energy budget components in a small scale basin to be detailed (e.g., references [69,70]).…”
Section: Experiments Design and Methodsmentioning
confidence: 99%
“…Six‐hourly precipitation time series provided by ARPEGE were aggregated to obtain daily rainfall, for which we applied the well‐known quantile–quantile correction. Such correction method enables to reduce biases through the entire range of the distribution (Gudmundsson et al ., 2012) and is particularly well adapted for extreme rainfall (Cantet et al ., 2014). Each station is associated with the nearest (land) model point (see Figure 2).…”
Section: Climate Model Outputs and Post‐processingmentioning
confidence: 99%